Sovereign Debt Exposure of European Less Significant Banks: Too Small to be Bailed (Revista Galega de Economía)
This paper studies the determinants of the sovereign debt portfolios of small European banks. We cover the time frame from 2010 to 2017, including the peak of the European debt crisis. Our analysis focuses on Less Significant Institutions (LSI), a group of small financial institutions that show a different sovereign risk exposure from larger institutions. Our results indicate that LSIs with strong credit quality and low capitalization tend to increase their investment in sovereign debt. We apply a GMM-system estimator to address endogeneity and unobserved heterogeneity. Overall, our results contribute to a better understanding of the risk determinants of LSIs, enriching the debate on supervision and regulation proportionality, as small European banks present distinctive behaviour. According to our results, a debate on macroprudential regulations to reconsider a country’s sovereign debt as risk free is desirable to reduce the risk exposure of LSIs.